Oncologic and Reproductive Outcomes of Uterine Smooth Muscle Tumor of Uncertain Malignant Potential: A Single Center Retrospective Study of 67 Cases - Huo, Lanqing; Wang, Dan; Wang, Wenze; Cao, Dongyan; Yang, Jiaxin; Wu, Ming; Yang, Junjun; Xiang, Yang (Frontiers in Oncology, 2020)
Background: The term “uterine smooth muscle tumor of uncertain malignant potential” (STUMP) indicates a rare tumor that cannot be classified as a benign leiomyoma or malignant leiomyosarcoma. In this study, we assessed the clinical characteristics, fertility, and oncologic outcomes of patients diagnosed as STUMP in 14 years. In addition, we analyzed the risk factors for recurrence in patients with STUMP. Methods: Medical records of STUMP patients at Peking Union Medical College Hospital (PUMCH) between January 2005 and June 2019 were reviewed and analyzed. Disease-free survival, age of diagnosis, tumor size, surgical procedure, pathology and immunohistochemistry, clinical characteristics, recurrence rate, and reproductive outcomes in the follow-up period were assessed. Univariate and multivariate analyses were performed to determine the prognostic factors. Results: The median age was 42 years old (range: 21-63). Total hysterectomy with or without bilateral salpingo-oophorectomy was performed in 29/67 cases (43.3%), and myomectomy was performed in 38/67 cases (57.6 %). Ten patients experienced recurrences, and all but one recurrence occurred within five years after the initial surgery. Only two of these recurrences were leiomyosarcoma. There were no deaths in the mean follow-up period of 50.6 (standard deviation, SD: 35.1) months. There were no remarkable differences in tumor size or location between the myomectomy and hysterectomy groups, but the patients in the myomectomy group were younger than those in the hysterectomy group. In univariate and multivariate analysis, mitosis on pathology was the only independent risk factor for recurrence. Expression of Ki-67, p53, and p16 was significantly higher in patients with recurrence. Seven of the thirty-five patients who attempted to conceive had successful pregnancies. The pregnancy rate was 20.0%. Conclusions: The prognosis of STUMP was good and tumors with more than ten mitoses per 10 high power field should be monitored closely. The surgical procedure was not an independent risk factor of recurrence, and myomectomy may be an acceptable option for patients wishing to preserve fertility.